Do Fraud Hexagon Components Promote Fraud in Indonesia? - Dio Alfarago; Azas Mabrur (Faculty of Economic and Business, 2022)
This study provides information about the likelihood of the natureof fraud companies so that investors and stakeholders can makebetter decisions. The Beneish model and the fraud theory aretwo well-developed ideas for understanding fraud motivationsand detecting earnings manipulation in a corporation. Unlikeprevious studies using the fraud triangle, this study uses the latesttheory (the fraud hexagon) perspective to detect fraud actions.Thus, this study aims to examine the applicability of the fraudhexagon components in combination with the M-score fromthe Beneish model. Seventy-six manufacturing firms listed onIndonesia Stock Exchange from 2015 to 2019 were chosen assamples. The findings confirmed that enterprises with fraud tendto: be more financially stable, be more leveraged, have higherprofitability, have cooperation projects with the government, havemore related-party transactions, have more auditor changes, beless liquid, less changing directors, be less supervised, and lessdisplay CEO.’s picture.JEL Classification: K40, K42